Наближення функцій багатьох змінних із класів BΩp,θ(Rd) цілими функціями експоненціального типу - Миронюк, В.В. (Український математичний журнал, 2014)
Получено декомпозиционное представление нормы функций многих переменных из пространств BΩp,θ(Rd) и установлены точные по порядку оценки приближений функций из единичных шаров этих пространств целыми функциями экспоненциального типа в пространстве Lq(Rd). We obtain the decomposition representation of the norm of functions of many variables from the spaces BΩp,θ(Rd) and establish the exact order estimates for the approximations of functions from the unit balls of these spaces by entire functions of exponential type in the space Lq(Rd).